The Athens of America : Boston, 1825-1845 - O'Connor, Thomas H., 1922-2012 (University of Massachusetts Press, 2006)
How Bostonians fashioned a shining image of their city in the early nineteenth century Many people are generally familiar with the fact that Boston was once known as "the Athens of America." Very few, however, are clear about exactly why, except for their recollections of the famous writers and poets who gave the city a reputation for literature and learning. In this book, historian Thomas H. O'Connor sets the matter straight by showing that Boston's eminence during the first half of the nineteenth century was the result of a much broader community effort. After the nation emerged from its successful struggle for independence, most Bostonians visualized their city not only as the Cradle of Liberty, but also as the new world's Cradle of Civilization. According to O'Connor, a leadership elite, composed of men of prominent family background, Unitarian beliefs, liberal education, and managerial experience in a variety of enterprises, used their personal talents and substantial financial resources to promote the cultural, intellectual, and humanitarian interests of Boston to the point where it would be the envy of the nation.; Not only did writers, scholars, and philosophers see themselves as part of this process, but so did physicians and lawyers, ministers and teachers, merchants and businessmen, mechanics and artisans, all involved in creating a well-ordered city whose citizens would be committed to the ideals of social progress and personal perfectibility. To accomplish their noble vision, leading members of the Boston community joined in programs designed to cleanse the old town of what they felt were generations of accumulated social stains and human failures, and then to create new programs and more efficient institutions that would raise the cultural and intellectual standards of all its citizens. Like ancient Athens, Boston would be a city of great statesmen, wealthy patrons, inspiring artists, and profound thinkers, headed by members of the "happy and respectable classes" who would assume responsibility for the safety, welfare, and education of the "less prosperous portions of the community."; Designed for the general reader and the historical enthusiast, The Athens of America is an interpretive synthesis that explores the numerous secondary sources that have concentrated on individual subjects and personalities, and draws their various conclusions into a single comprehensive narrative